Remisi hukuman dan konstitusionalitas hukuman penjara seumur hidup di Seychelles - Jamil Ddamulira Mujuzi (Badan Strategi Kebijakan Hukum, 2024)
This article critically examines the legal framework surrounding life imprisonment in Seychelles, particularly in light of recent legislative and judicial developments. Historically, Seychelles' legal landscape allowed for the remittance of sentences for all prisoners except those serving life terms or convicted of severe drug offenses. Prior to 2021, ambiguity existed regarding whether life imprisonment necessitated incarceration for the entirety of an offender's life, leading to varied interpretations and inconsistent practices wherein some individuals were released after 15 to 20 years of imprisonment. This uncertainty was addressed by an important decision of the Seychelles Court of Appeal, which asserted that life imprisonment should indeed mean incarceration for the remainder of the convict's natural life. Subsequently, legislative amendments in 2021 codified this understanding within the Criminal Procedure Code, expressly defining life imprisonment as confinement for the duration of the offender's life. However, the article argues that such a statutory definition and practice may contravene fundamental human rights principles, particularly concerning human dignity and protection from inhuman or degrading treatment. Drawing on comparative jurisprudence from various African jurisdictions, decisions of the European Court of Human Rights, and standards articulated by international human rights bodies, the author contends that indefinite life imprisonment without the prospect of release violates prisoners' rights enshrined in international law. Furthermore, the author invokes the drafting history of Article 10(3) of the International Covenant on Civil and Political Rights (ICCPR), emphasizing that the intent behind the provision was to safeguard against overly punitive sentences that deny any possibility of rehabilitation or eventual release. This historical context, according to the article, supports the argument that Seychelles' current approach to life imprisonment undermines its obligations under international human rights norms. Moreover, the Constitution of Seychelles grants the President discretionary powers under Article 60 to commute sentences, theoretically enabling the release of individuals sentenced to life imprisonment. This aspect introduces a layer of executive discretion that intersects with constitutional principles and international human rights standards, warranting further examination and critique. In conclusion, the article posits that Seychelles' statutory definition of life imprisonment raises constitutional and human rights concerns, advocating for a reevaluation of current practices in light of international legal standards and principles of justice.